UPAYA PENINGKATAN PEMBELAJARAN TOLAK PELURU DENGAN PENDEKATAN PERMAINAN SIRKUIT PADA KELAS V SEKOLAH DASAR NEGERI 1 ROWOSAR KECAMATAN ROWOSARI KABUPATEN KENDAL TAHUN 2013 (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
The purpose of this study was to determine the increase in student learning outcomes in learning through play shot-put circuit in fifth grade Elementary School District 1 Rowosari Rowosari Kendal District . This study uses action research . The subjects were students of class V Rowosari Elementary School District . Rowosari Kab . Kendal . Techniques of data collection using the test methods , methods of documentation , and questionnaires . The results of this study are based on survey data . Student learning outcomes in the first cycle and the second cycle of action . In the first cycle, the percentage of the total acquisition of the learning achievement of 64% and this achievement is increased by 21 % to 85 % . Increasing the learning process would logically lead to greater student achievement, which in this context is the increasing ability of students to reject bullets . Conclusions of research is learning through play circuits can improve learning outcomes Elementary School fifth grade students of the District 1 Rowosari Rowosari Kendal in the Academic Year 2012/2013 . Research suggestions include a few things , namely : 1 ) The game can be an alternative circuit for teachers Penjasorkes to apply the material in Shot Put , 2 ) Teacher Penjasorkes to improve competence in designing , preparing , implementing and evaluating learning through a variety of sources Â